Increases of Offshore Wind Potential in a Warming World - Cheng Shen; Zhi‐Bo Li; Hui‐Shuang Yuan; Yue Yu; Yadong Lei; Deliang Chen (Geophysical Research Letters)
Abstract Offshore wind farms, a rapidly expanding sector within wind energy, are playing a significant role in achieving global carbon neutrality, and this trend is to continue. Here, we utilize ERA5 reanalysis to correct offshore wind speed trends predicted by CMIP6 models. This approach led to enhanced projections for changes in offshore Wind Power Density (WPD) under four Shared Socioeconomic Pathways (SSPs) scenarios. Throughout the 21st century, global offshore WPD is projected to follow an upward trend across all SSP scenarios. Notably, Europe stands out with the most substantial increase in offshore WPD among regions with higher current installations, projected to reach up to 26% under 4°C global warming. Our study uncovers a notable increase of global offshore WPD in a warmer climate, which offers valuable insights for the strategic planning of future global wind energy.